Aristotle in the Anthropocene: the comparative benefits of Aristotelian virtue ethics over Utilitarianism and deontology - Morrell, Kevin; Dahlmann, Frederik (SAGE, 2022)
In the Anthropocene, humanity faces a pressing question: ‘what should we do?’ Here we are interested in the underlying sense and reference of the normative ‘should’ as it applies to ethics with respect to different actors. To excavate ‘should’, we unearth the foundations of three conventional groupings of normative ethical systems: Mill’s utilitarianism, Kantian deontological ethics and Aristotelian virtue ethics. Each provides a normative basis for saying what humans ‘should’ do. We draw on specific examples from the private sector to argue that debates on the role of ethics in business are dominated by consequentialist and deontological accounts which, while essential, entail certain limitations regarding the realities of this new geological epoch. Identifying the comparative benefits of Aristotelian virtue ethics enables us to develop new insights and suggestions for ethics in the Anthropocene. We identify three distinctive features of Aristotelian virtue ethics: (i) a focus on agents rather than acts, (ii) a distinction between laws and customs versus nature and (iii) the importance of tradition. We set out corresponding implications for ethics and sustainability as applied to the private sector.
Keywords: Anthropocene; Aristotle; business; sustainability; virtue